Formation of an open educational environment using artificial intelligence technologies: analysis and classification - Kruglyk, Vladislav; Osadchyi, Viacheslav; Pavlenko, Liliya; Symonenko, Svitlana (Educological discourse, 2024)
The article explores the possibilities of using artificial intelligence technologies to create an open educational environment. Specific artificial intelligence tools and services for use in the educational process are analysed. The authors classify artificial intelligence tools according to their functionality in key areas such as learning, teaching, assessment, and administration. The analysed tools include: Knewton, ALEKS, DreamBox, Edmodo, Grammarly, Speechify, Synthesia, ChatGPT, and others. It is concluded that artificial intelligence technologies allow creating an open educational environment with personalised, adaptive learning, automated assessment, and effective management. The article describes typical ways of using artificial intelligence in education for learning (assigning personalised tasks, providing interactive dialogue, analysing students’ learning activities), teaching (increasing the adaptability of teaching methods and developing the professional competence of teachers), assessment (automation of knowledge control processes, prediction of student performance, creation of assessment tools), and administration (analysis of educational data, making informed management decisions). At the same time, it is necessary to take into account the potential risks and ethical issues with respect to the introduction of artificial intelligence into education. For further research, the authors suggest practical testing of approaches, analysis of economic aspects, and the study of the application of sectoral features of artificial intelligence. The results of the study are valuable for determining the optimal strategies for integrating artificial intelligence into the educational environment to improve the quality of education and ensure the innovative development of the industry.